3√12-2√27=
4supra3 / 2supra9=
0,2supra0,01=
(2supra3)²-0,(4)=
Răspunsuri la întrebare
Răspuns de
2
3√12=3x2√3=6√3
2√27=2x3√3=6√3
3√12-√27=6√3-6√3=0
(4/3)/(2/9)=4/3:2/9=4/3x9/2=(4x9)/(3x2)=36/6=6
0,2/0,01=0,2:0,01=2/10:1/100=2/10x100/1=200/10=20
(2/3)²-0,(4)=(4/9-4/9=0
2√27=2x3√3=6√3
3√12-√27=6√3-6√3=0
(4/3)/(2/9)=4/3:2/9=4/3x9/2=(4x9)/(3x2)=36/6=6
0,2/0,01=0,2:0,01=2/10:1/100=2/10x100/1=200/10=20
(2/3)²-0,(4)=(4/9-4/9=0
ionutdiaconu371:
va multumesc
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă